Sox2-overexpressing neural stem cells alleviate ventricular enlargement and neurological dysfunction in posthemorrhagic hydrocephalus - Baocheng Gao; Haoxiang Wang; Shuang Hu; Kunhong Zhong; Xiaoyin Liu; Ziang Deng; Yuanyou Li; Aiping Tong; Liangxue Zhou (Neural Regeneration Research)
Neural stem cells (NSCs) have the potential for self-renewal and multidirectional differentiation, and their transplantation has achieved good efficacy in a variety of diseases. However, only 1%–10% of transplanted NSCs survive in the ischemic and hypoxic microenvironment of posthemorrhagic hydrocephalus. Sox2 is an important factor for NSCs to maintain proliferation. Therefore, Sox2-overexpressing NSCs (NSCSox2) may be more successful in improving neurological dysfunction after posthemorrhagic hydrocephalus. In this study, human NSCSox2 was transplanted into a posthemorrhagic hydrocephalus mouse model, and retinoic acid was administered to further promote NSC differentiation. The results showed that NSCSox2 attenuated the ventricular enlargement caused by posthemorrhagic hydrocephalus and improved neurological function. NSCSox2 also promoted nerve regeneration, inhibited neuroinflammation and promoted M2 polarization (anti-inflammatory phenotype), thereby reducing cerebrospinal fluid secretion in choroid plexus. These findings suggest that NSCSox2 rescued ventricular enlargement and neurological dysfunction induced by posthemorrhagic hydrocephalus through neural regeneration and modulation of inflammation.